Agile Development of PressAI: Enhancing Educational Efficiency through QR-Based Attendance and AI-Powered Essay Scoring - M. Miftach Fakhri; Pramudya Asoka Syukur; Muh Idul Akbar Pratama; A.M Yusran Mazidan; Alya Olivia; Rosidah (Jurusan Teknik Informatika dan Komputer, 2024)
In learning activities, common issues such as time-consuming and manipulation-prone attendance processes, as well as subjective and inconsistent essay grading, often arise. This study aims to develop PressAI, an AI-based application that automates attendance using QR code technology and provides objective essay grading powered by the OpenAI API. The application was developed using the Agile methodology integrated within the Software Development Life Cycle (SDLC) framework, through iterative stages including planning, requirements analysis, system design, implementation, and testing. The results demonstrate that PressAI enables instant and accurate attendance recording via QR scanning, provides a seamless login experience without repeated authentication, and delivers fast and objective essay assessments. With its features, PressAI is expected to enhance efficiency and transparency in the learning process while offering opportunities for further innovative feature development.